Reference module in chemistry, molecular sciences and chemical engineering - Reedijk, Jan (Elsevier, 2013)
This Reference Module contains peer-reviewed, comprehensive content from our reference works as curated by our world-class editorial board led by Editor-in-Chief, Jan Reedijk. It is designed for faster, more relevant browsing within the subject and beyond, with topic pages for quick, clear overviews, subject hierarchies to put everything in context, and guidance to lead researchers to related knowledge